Analysis Of Implementation Of Talent Management On The Management Of The Santri Organization Darussalam Islamic Boarding School - Heru heryanto, Jurnal manajemen talenta ukri; Sadikin, Bahrul; Sadikin, Elihu; Agustina, Granit (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2025)
The purpose of this study is to analyze how talent management is implemented in the student organization of the Darussalam Kunir Islamic Boarding School, especially among its administrators. This study focuses on the development and improvement of the quality of the management of the student organization, as well as the impact of the implementation of talent management on the students. The method used in this study is qualitative descriptive, with data collection through interviews and observations of participants such as the advisory board, the head of the organization, and several representatives from the management department. The results of the study indicate that the student organization at the Darussalam Kunir Islamic Boarding School implements an effective talent management strategy, which includes the selection and recruitment of administrators, recruitment criteria, continuous skill development, and performance assessment. The conclusion of this study emphasizes the importance of an integrated approach to continuously improve the quality of the management of the student organization and strive to achieve the vision and mission of the Islamic boarding school.